Structural, optical, photoluminescence and radiation-shielding investigation of magnesium doped barium zirconate (BaZrO 3 ) ceramics - Ghrib, T.; Ben Ali, A.; Ercan, F.; Mhareb, M. H. A.; Al-muteliq, S. Y.; Ercan, I.; Younas, M. (Pergamon-Elsevier Science Ltd, 2024)
Magnesium-doped barium zirconate (BaZrO3) powders with various Mg atomic ratios (0.1, 0.2, 0.3, 0.4, and 0.5) have been synthesized by using the solid-state reaction method. The structure and microstructure were studied via scanning electron microscopy, X-ray powder diffraction (XRD), energy dispersive X-ray (EDX), Raman, and Fourier transform infrared (FTIR) spectroscopy. The optical properties were investigated using UV-Vis and photoluminescence spectroscopy. XRD results showed that the synthesized powders have a cubic crystal system with a grain size in the range of 23-27 nm. The band gap is estimated to be about 3.5-3.59 eV. The photoluminescence shows UV and visible emissions. The neutron and gamma shielding features were calculated and assessed based on Phy-X software of energies ranging from 0.015 to 15 MeV. The gamma shielding parameters were generally reduced by adding Mg instead of Ba. The neutron shielding parameter was enhanced gradually. Based on these results, the ability to use the synthesized samples in radiation and neutron shielding applications can be deduced.
Keywords: Mg dopedBaZrO(3); XRD; FTIR; Radiation shielding; Band gap; Photoluminescence